Growth of Global Over-the-Top and Korean Media Market: Competition and Regulatory Policy Issues - Sangwon Lee; Seonmi Lee; Justin Brown (International Telecommunications Society (ITS), 2017)
Global markets for OTT (Over-the-Top) services are growing. Focusing on OTT services in Korean media markets, this study explores technological, industrial, and policy factors in OTT markets. Specifically, platform competition and regulatory classification for market entry regulation, global OTT players' negative impacts on national economy, reverse discrimination against domestic players and user protection issues are discussed. Based upon the discussion on competition and policy issues for OTT players, this study suggests future policy directions for Korean media markets.
Keywords: 330; Global Over-the-Top; Regulatory Policy; Korea; Platform Competition